Adaptation of Collins Revised Adult Attachment Dimensional Scale to the Chilean Context - Fernandez-Tapia, A (Universidade Federal do Rio Grande do Sul, 2015)
The Adult Attachment Revised Scale is a measure of relationship attachment that contains three dimensions: closeness, dependence and anxiety. In Study 1, the scale was translated and applied to a sample of 420 university students in order to assess reliability. In addition, the scale criterion validity was estimated through measures of self-perception and affectivity. The results of Study 1 supported the internal consistency of two dimensions of attachment, but dependence was lower than expected (α = .62). A confi rmatory factor analysis was conducted and failed to reach a convergent fi t, thus demonstrating that two of the items in dependence were considered problematic. In Study 2, diffi cult items in Study 1 were reworded and the new version of the scale was applied to 81 participants. The results of two subsequent CFAs showed adequate fi t of the scale and increased internal consistency with this new wording (α > .73), which replaced the expression "depend on others" by "getting help from others", which is a better construct representation of the meaning of dependence in the context of attachment closeness. Therefore, not only did we adapt the three dimensions of the attachment scale, but also provided evidence of its validity related to locally adapted instruments.